2023
DOI: 10.3389/ijph.2023.1605688
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Insomnia on Burnout Among Chinese Nurses Under the Regular COVID-19 Epidemic Prevention and Control: Parallel Mediating Effects of Anxiety and Depression

Abstract: Objective: To investigate the mediating effects of anxiety and depression in the relationship between insomnia and burnout among Chinese nurses under the regular COVID-19 epidemic prevention and control.Methods: Convenience sampling was applied to recruit 784 nurses in Jiangsu Province, China. The respondents completed the survey via mobile devices. Demographic questionnaire, Insomnia Severity Index, Generalized Anxiety Disorder-7, Patient Health Questionnaire-9 and Maslach Burnout Inventory were used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…However, opposite results were detected among PA and variables of interest. The results above were consistent with those of prior research (Yang, 2011 ; Liu et al, 2023 ; Mao et al, 2023c ). For example, Liu and colleagues found that PTSD was significantly and positively correlated with burnout, whereas social support and resilience were significantly and negatively related to burnout among medical staff two years after the COVID-19 pandemic in Wuhan, China (Liu et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, opposite results were detected among PA and variables of interest. The results above were consistent with those of prior research (Yang, 2011 ; Liu et al, 2023 ; Mao et al, 2023c ). For example, Liu and colleagues found that PTSD was significantly and positively correlated with burnout, whereas social support and resilience were significantly and negatively related to burnout among medical staff two years after the COVID-19 pandemic in Wuhan, China (Liu et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…For example, Liu and colleagues found that PTSD was significantly and positively correlated with burnout, whereas social support and resilience were significantly and negatively related to burnout among medical staff two years after the COVID-19 pandemic in Wuhan, China (Liu et al, 2023 ). Mao et al detected significantly and positively moderate correlations among anxiety, depression, insomnia and burnout among Chinese nurses under regular COVID-19 epidemic prevention and control (Mao et al, 2023c ). Meanwhile, self-efficacy was negatively correlated with burnout among Korean psychiatric nurses who provided care for patients with mental illnesses and infections with COVID-19 (Lim et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The indirect effects as per unstandardized coefficients (b) and bias-corrected 95% confidence intervals (CIs) were computed based on 200 bootstrap replications drawn from the original 307 subjects. The presence of a mediating effect was accepted if the 95% CI did not cross zero (Mao et al, 2023). All tests were two-tailed with a significance level of α = 0.05.…”
Section: Statisticsmentioning
confidence: 99%